The impact of debt on tax avoidance: Evidence from companies listed on the Korean stock market - Kwon, Gee-Jung (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of corporate debt levels on tax avoidance among companies listed on the Korean stock market from 2001 to 2023. Using eight empirical models, the analysis examines the relationship between corporate debt and firm value (Models 1–4) and the effects of debt level fluctuations on corporate value (Models 5–8). The findings indicate that corporate debt serves as a mitigating factor for tax avoidance, as evidenced by a negative correlation between debt levels and tax avoidance measures (DDBTD, BTD). This supports the primary hypothesis that higher corporate debt levels are associated with lower tax avoidance activities. Additionally, changes in debt levels, whether increases or decreases, consistently exhibit a negative relationship with tax avoidance. This result reinforces the secondary hypothesis that fluctuations in corporate debt further reduce tax avoidance behavior. These findings suggest that Korean listed firms utilizing external debt financing to enhance internal cash flow and benefit from interest expense deductions tend to engage less in tax avoidance. This study contributes to the literature on corporate financial behavior by highlighting the role of debt financing in shaping tax planning strategies. The results provide practical implications for policymakers and corporate decision-makers concerned with tax compliance and financial management.